2015
DOI: 10.1042/bj20140203
|View full text |Cite
|
Sign up to set email alerts
|

The eukaryotic elongation factor eEF1A1 interacts with SAMHD1

Abstract: Mutations in SAMHD1 cause Aicardi-Goutières syndrome (AGS), a Mendelian inflammatory disease which displays remarkable clinical and biochemical overlap with congenital viral infection. SAMHD1 (SAM domain and HD domain-containing protein 1) has also been defined as an HIV-1 restriction-factor that, through a novel triphosphohydrolase activity, inhibits early stage HIV-1 replication in myeloid-derived dendritic cells (MDDCs), macrophages and resting CD4+ T-cells. The potent activity of SAMHD1 is likely to be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…33,34,41 It participates in several processes required for proliferation, mitotic apparatus formation, and signal transduction. [34][35][36] In a previous study, it was reported that elongation factor 1-alpha 1 is differentially expressed in PDL cell in presence of enamel matrix protein in culture medium. Increase was demonstrated in RNA synthesis, which causes periodontal regeneration and wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…33,34,41 It participates in several processes required for proliferation, mitotic apparatus formation, and signal transduction. [34][35][36] In a previous study, it was reported that elongation factor 1-alpha 1 is differentially expressed in PDL cell in presence of enamel matrix protein in culture medium. Increase was demonstrated in RNA synthesis, which causes periodontal regeneration and wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we visualized dendritic localization of eEF2 but not of eEF1a in NL neurons, suggesting that FMRP may affect dendritic protein synthesis by modulating a subset of translational regulatory machinery. Although a direct link between FMRP and eEF1a and eEF2 mRNAs has not been demonstrated, both of these two elongation factors have been associated with potential roles in cellular growth/proliferation and signal transduction (Lin, Yakymovych, Jia, Yakymovych, & Souchelnytskyi, ; Morrissey et al, ) as well as synaptic regulation (Becker, Kuhse, & Kirsch, ; Mateyak & Kinzy, ; Rosenblum, Meiri, & Dudai, ). In particular, eEF2 has recently been considered as a biochemical sensor that couples neuronal transmission to spine plasticity, a major proposed function of FMRP signaling (Verpelli et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies however, have exposed protein interaction partners that provide clues as to the mechanism of normal SAMHD1 degradation. SAMHD1 interaction with both cyclin L2 and eukaryotic elongation faction 1A1 (eEF1A1) facilitates recruitment to the ubiquitin ligase machinery and subsequent proteosomal degradation (113, 114). A more recent study suggests that interaction with the transmembrane tetraspanin CD81 promotes proteosomal turnover of SAMHD1 (115).…”
Section: Samhd1 Cellular Regulation and Nucleotide Metabolismmentioning
confidence: 99%